IMPLEMENTATION SERVICE RIGHT ASSIMILATION IN HOUSE FOR PRISONERS DURING THE COVID PANDEMIC 19IN CLASS IIA PURWOKERTO PRISON - Ervan Miftahul Alim; Taufik Purboyo; Emiraldo Win.P (DYNAMICS: Journal of Public Administration, 2022)
This study is entitled "Implementation of Home Assimilation Rights Services for Inmates During the Covid 19 Pandemic in Class IIA Prisons in Purwokerto. The purpose of this study is to describe and explain the implementation of assimilation rights services at home for prisoners during the Covid-19 Pandemic in Class IIA Prison Purwokerto, Banyumas Regency. This research was conducted at the Class IIA Prison, Purwokerto, Sokaraja District, Banyumas Regency. The method of this research is descriptive qualitative. Informants were determined by purposive sampling method. The analysis of research results using an interactive analysis model.Based on the results of the study, several conclusions can be drawn asfollows:(1). The size and purpose of the policy, the granting of prisoners' rights at the Class IIA Purwokerto Prison is in accordance with the legislation, the guidance carried out at the Class IIA Purwokerto Prison aims to return prisoners to the community by providing life provisions, there are many personality and skill development activities that can be followed by inmates at the Class IIA Purwokerto Prison.(2).Resources, services provided immediately, accurately and satisfactorily, such as punctuality, speed and accuracy in the service of prisoners' rights, in the implementation of prisoner development there are facilities and infrastructure to support prisoners' activities.(3). Characteristics of the implementing agency/agency, In the assimilation policy at home during the covid-19 pandemic which was carried out at the Class IIA Purwokerto Prison, the implementing agents involved included correctional guardians, BAPAS, prisoners and third parties. There is a well-established communication so that the implementation of the right of assimilation is timely, there is cooperation with partners in the implementation of skills development for prisoners.(4). The attitude/tendency of the implementers, the implementation of the home assimilation program policy during the covid-19 pandemic, there was no rejection from the Purwokerto Class IIA Penitentiary and inmates, the officers provided coaching with persuasive methods, the absence of recidivists was an indicator of the success of the assimilation program.(5). Communication between organizations and implementing activities, in carrying out assimilation at home during the covid-19 pandemic, prisoners are required to take part in coaching activities carried out in prisons, there is cooperation with related parties to make the assimilation program at home successful during the COVID-19 pandemic.(6). The economic, social, and political environment, internal obstacles so that the service process for the rights of prisoners is hampered, there are various responses related to the home assimilation program for prisoners in the community, prisoners have been equipped and assisted by prison officers in developing skills for capital to return to society.Implication: To improve service quality, efforts need to be made: (1) Add office service facilities (2) Communication with third parties needs to be improved (3) It is necessary to add infrastructure for the activities of fostering prisoners (4) There needs to b a rewards for prisoners who active participate in coaching.